Peran Badan Usaha Milik Desa (BUMDes) Berkah Dalam Memberdayakan Masyarakat Melalui Pengelolaan Pasar Tradisional Di Desa Bulang Kabupaten Muara Enim - Alviani Alviani; Shomedran Shomedran (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to analyze the role of Village Owned Enterprises (BUMDes) in advancing society through the management of traditional markets in Bulang Village, Muara Enim Regency. This study used a qualitative descriptive method with data collection techniques through interviews, observation, and documentation of six respondents. The results of the study show that BUMDes have succeeded in increasing the income and economy of the community through four objectives of establishment: advancing the village economy, increasing village original income, optimizing local potential, and encouraging growth and economic equality. This has a positive impact on the community's economy. The quality of life in Bulang Village has increased related to: increased income, decent housing, healthy environment, social stability, health, education and job opportunities. Rural economic growth in Bulang Village achieves the characteristics of good economic growth, including rapid per capita product growth, increased community productivity, structure, and a significant level of urbanization. This shows that BUMDes plays an important role in driving the economy and improving the quality of life of village communities